Le bloc-diagramme comme outil d’analyse du paysage et de ses représentations dans la plaine d’inondation du lac Janauáca, Amazonie, Brésil - Lainé, Juliette (Sustainability in Debate, 2013)
This work presents a landscape analysis and discusses its representations among the communities of Janauáca’s lake, 60 km far from Manaus, in the Solimões River’s floodplain. This area has recently become the scene of deep social and environmental changes that stigmatize the landscape. The acceleration of hydrologic extremes, as the flood of 2012, is threatening the populations of ribeirinhos. In this landscape of dynamic configuration, various actors and representations of nature are confronted. Sustainable solutions make it necessary to define the concept of socio-environmental diversity. The adopted methodology includes the analysis of two main sources of data: speeches (semi-directive interviews) and pictures (draws and photography workshops, participant observation). The data is used to construct some 3D mapping that represents natural characteristics, the actors influences, and the dynamic and challenges in the mean zones of the lake. The analysis highlights a landscape mutation that showcases a conflict between economic development and ecological sustainability. Among the actors of the landscape, we have identified four socio-environmental profiles, acting differently in front of the variability of the várzea middle area.